Industrial activity, energy structure, and environmental pollution in China - Chen, Lei; Li, Ke; Chen, Shuying; Wang, Xiaofei; Tang, Liwei (Energy economics, 2021)
This study investigated the impact of industrial activity and energy structure on environmental pollution from the demand and supply side with the panel data source from 2000 to 2016 of 30 provinces in China. Empirical results show that, in the long-term, increasing R&D investment, improving industrial energy efficiency, and adjusting the coal consumption structure can reduce the pollution emissions significantly. However, the environmental pollution treatment investments and the capital-embodied technological progress have different impacts on various emissions. Specifically, the former reduces the total emissions but does not impact the emissions intensity; the latter, namely, capital-embodied technological progress, can reduce wastewater emissions because of the possible performance of capital quality upgrading. In the short-term, only coal consumption structure and capital-embodied technological progress have similar effects on the pollution emissions as they are in the long term, reflecting that the policymaking is different in the short-term and long-term. Furthermore, this study confirms that environmental regulations affect industrial pollution through energy efficiency and energy structure changes. The findings show that adjusting the energy structure is the primary channel to emissions reduction. •Empirical model was constructed from demand and supply side and data are from China.•Impacts of different types of technological progress on pollution was studied.•Panel cointegration model and panel vector error-correction model was used.•capital-embodied technological progress has different impacts on various emissions.•Driving forces' effects on pollution are different in long-term and short-term.